BIODEGRADATION OF DISPERSED HETEROCYCLIC TEXTILE AZO DYE BY BACTERIA ISOLATED FROM DUMPING GROUND NEAR BOISAR (International Journal of Food and Nutritional Sciences, 2022)
Azo dyes are the most important synthetic colorants which have been widely used in textile, printing, paper manufacturing, etc. One of the class of azo dyes that finds a wide application in the textile industry for its intense colouration and excellent dyeing properties is Dispersed heterocyclic azo dyes. The extensive use of these dyes has added to one of the major environmental pollutants causing harm to flora and fauna of the ecosystem in which it is released as effluent from the textile industry. In the present study the disperse heterocyclic azo dye was decolourized by the bacteria isolated and selected from the dumping grounds of Khaira Phata, Boisar by Replica plate technique. The growth of bacteria and decolourization of the dispersed heterocyclic azo dye was observed around the colonies obtained on replica plates embedded with 400 ppm of Disperse Blue. Optimization of the conditions (Temperature and Static and shaker conditions) was done to efficiently decolourize the Disperse Blue. The % efficiency of decolourization was determined spectrophotometrically at 580 nm. Culture No. 3 decolourized the dye efficiently to 53.75% under Static conditions at room temperature.